Digital Innovation for Monitoring the Mental Health of Students at UPN "Veteran" East Java Using the PHQ-9 Instrument - maulana, Hendra; Citra, Delia; Sari, Lintang; Safana, Tsabita; Aprilia, Erica (Jurnal Teknokes, 2025)
Mental health issues, especially depression, are increasingly prevalent among university students in Indonesia, primarily due to academic, social, and emotional pressures during the transition from adolescence to adulthood. This study developed and evaluated UWAYS, a mobile application designed to assist the early detection of depressive symptoms using the Patient Health Questionnaire-9 (PHQ-9). The app features include an interactive PHQ-9 self-assessment,  historical tracking of assessment results, and automatic initial recommendations based on score classifications. Involving 100 active students of UPN “Veteran” East Java, the results showed that most participants fell  within the mild to moderate depression categories, with sleep disturbance and low self-confidence as the most common symptoms. The System Usability Scale (SUS) assessment yielded an average score of 77.3, indicating good usability and positive user acceptance. These findings confirm that UWAYS provides an accessible, practical, and user-friendly tool for independent mental health screening among students. This application serves as an initial step to support mental health management in the campus environment and offers potential for further integration with university counseling services. The study also highlights that the lack of early detection mechanisms on campus remains a gap that can be addressed through digital innovation like UWAYS, which combines scientific accuracy, data confidentiality, and ease of use to encourage proactive mental health awareness among students.